G 6PD DEFICIENCY AND BETA-THALASSAEMIA IN THE SAME PATIENT - Khan, Mir Hassan; Khan, Jahangir A.; Raziq, Fazle (Journal of Ayub Medical College Abbottabad, 1990)
Abstract: A report of 8 months old female child with a rare combination is presented who had inherited G6PD deficiency from father and Bela-Thalassaemia from mother.